Clinical supervisory tasks for speech pathology clinical supervisors video instructional material on demonstration, observation and feedback - Ligot, Fernando Alejandro C. (1997)
A video instructional material (VIM) on demonstration, observation and feedback was produced and evaluated by two groups of reviewers. The first group of reviewers, the Peer Reviewers was composed of faculty members of the UP-CAMP's Occupational, Physical Therapy and Speech Pathology departments. The second group of reviewers, the Expert Reviewers was composed of speech pathology clinical supervisors. The Peer reviewers were tasked to evaluate the technical aspects of the VIM. The Expert were tasked to evaluate the content of the material. The objective of the study was to produce a training material for speech pathology clinical supervisors, based on a survey conducted among three groups: speech pathology interns, speech pathology clinical supervisors and professional speech pathologists, determining the supervisory tasks of speech pathology clinical supervisors. At the end of the survey stage, three supervisory tasks were identified as primarily significant to student learning, namely, demonstrating, observing and giving feedback. Having identified these tasks a script for modeling of the said tasks was written and video recording ensued. Simultaneous with the video recording a discussion guide was also written to accompany the video instructional material. The discussion guide will be used to facilitate a discussion whenever the VIM will be used for training or teaching. The VIM contained dramatized video segments of demonstration, observation and feedback. The development of the video went through several stages. The initial stages included the writing of the script, identifying scenarios, and writing a temporary drawing board. The second stage involved video recording the presentation. Five segments were video recorded: 1) pre-session conference, 2) demonstration process, 3) post-session conference, 4) observation and, 5) giving feedback. Videotaping and post production editing took two days each. A professional video production outfit was commissioned to perform the post production work. Once a final copy of the video was produced, the third stage of the study took place, the evaluation phase. Two groups of evaluators were included in this phase, the peer reviewers and the expert reviewers. The peer reviewers evaluated the technical aspects of the video while the expert reviewers evaluated the content. For their evaluation, a set of checklists were prepared. Since each group was tasked to evaluate a different aspect two different checklists were used. The checklists were patterned after existing assessment instruments for instructional materials, although there were some modifications done to suit the purpose of the study and the evaluation. A single viewing sessions was scheduled for both groups of reviewers. When evaluation was done, the results were tabulated and analyzed qualitatively. The discussion of the results focused on the positive as well as the negative responses given by the evaluators. The evaluation done by the Peer and Expert reviewers also showed very interesting results. Even though they evaluated different aspects of the material, both groups agreed that the VIM contained appropriate objectives, that the supervisory tasks were significant to clinical teaching and relevant to student learning. They also agree on the sources of the objectives as coming from faculty development needs and a learning approach, meaning the creation of the VIM arose from these above mentioned educational needs. Generally, both groups found the material to be a useful training material for prospective clinical supervisors as well as teaching instrument for pre-clinical students. Needless to say that the educational value of the VIM has been realized by the reviewers, implying that the VIM is an acceptable training material for speech pathology clinical supervisors.